MENUMBUHKEMBANGKAN NASIONALISME PESERTA DIDIK MELALUI KEGIATAN PRAMUKA DI SMA MUTIARA BANGSA GUNUNG KALER - Kabir Kabir (STAI Darul Qalam Tangerang, 2021)
This program is created to develop students' nationalism through scouts activity in SMA Mutiara Bangsa Gunung Kaler. The results are 1) so-cialization is done accurately by spreading questionnaire to all study group start from class 10th, 11th, as well as 12th grade, so that they can attend the scout activities, which is hold by school including some aspects such as introduction nationalism relate to explanation of scouting especially about national principle Pancasila, UUD 1945, and introduction to Indonesian culture; 2) The result of evaluation shows that students at SMA Mutiara Bangsa Gunung Kaler are actively attend the scouting activities that has scheduled, so that, it can be known the result from average of students before and after joining the scout activities actively. In this case, data is obtained from SMA Mutiara Bangsa Gunung Kaler, as like the result of observation